The Relationship between Acute-to-Chronic Glycemic Ratio and SYNTAX Score in Diabetic Patients Presenting with Acute Coronary Syndrome - Demir, Ömer Furkan; Balyimez, Ayşe Dilara (International Journal of Angiology, 2023)
A new index called the acute-to-chronic (A/C) glycemic ratio has been proposed to better represent the true acute glycemic rise in people with acute disease. However, there has been no previous study investigating the relationship between A/C glycemic ratio and SYNTAX score in patients with diabetic acute coronary syndrome (ACS). The aim of this study is to evaluate the role of A/C glycemic ratio in predicting coronary artery disease severity and SYNTAX score in diabetic patients presenting with ACS. The study included 131 consecutive patients hospitalized for ACS in our hospital, previously diagnosed with diabetes and undergoing percutaneous coronary intervention. The relationship between A/C glycemic ratio and SYNTAX score calculated at the time of admission was determined in univariate and multivariate linear regression analyses. The sample size was divided into three parts (T1, T2, and T3) according to the admission blood glucose (ABG)/estimated average glucose (eAG) ratio. When ABG/eAG and SYNTAX scores were compared, there was no significant difference between the T1 and T2 groups, but a significant increase was found in the T3 group compared with the other two groups (T1: 14.26, T2: 14.77, T3: 24.41; p < 0.001). When multivariate modeling was performed with the two or three most relevant variables (age, estimated glomerular filtration rate [eGFR], and ABG/eAG ratio), the upper tertile of the ABG/eAG variable was correlated with the severity of coronary atherosclerosis and higher SYNTAX score. This study shows that there is a significant relationship between higher ABG/eAG ratio and higher SYNTAX score in diabetic patients presenting with ACS.
Keywords: acute coronary syndrome; diabetes mellitus; HbA1c; acute-to-chronic glycemic ratio; SYNTAX score; coronary artery disease